(untitled) (Jurnal Geomine, 2022)
The research location in the Latuppa area, located in Mungkajang District, Palopo, South Sulawesi, is an area with a fairly wide spread of granodiorite so it is important to study these rocks because they can show the presence of minerals that have sufficient potential to be excavated, mining as an economical mineral. This research is intended to make an analysis covering the Petrogenesis and Geotectonics of Granodiorite Rocks. Based on the megascopic and petrographic analysis of Granodiorite rocks, the descriptions are holocrystalline, phaneric, euhedral to subhedral, equigranular, massive structure. Based on the weight ratio plot (%) of K2O and SiO2 in magma affinity classification, the magma series is divided into two, namely High-K Calc–Alkaline. The content of "SiO2 and Na2O + K2O" the classification is Granodiorite. This rock belongs to the class peraluminious S - type granite,from the geochemical analysis and microscopic description of Latuppa granodiorite rocks formed on the Active Continental Margin.